Pengaruh ROE, PER, DPR, DER dan EPS terhadap Harga Saham Studi Empiris di BEI Tahun 2011-2014 - Gunawan Raspati (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2019)
This study was conducted to analyze the influence of Return On Equity ratio (ROE), Price Earnings Ratio (PER), Dividend Payout Ratio (DPR), Debt to Equity Ratio (DER) and Earnings Per Share (EPS) to the stock price and to identify independent variables that most influence on stock prices. This study uses secondary data from the financial statements of 47 companies listed on the Indonesia Stock Exchange that consistently pay dividends during the period 2011 through 2014. The research found that the ROE and EPS have a significant positive effect on stock prices, while the PER, DPR, and DER have no significant impact on stock prices. EPS is the most dominant variable affecting the stock price. The indication is the investor prefers to buy the shares of companies with an excellent performance that reflected on the ROE and gives a high return that reflected on the EPS.